2002
DOI: 10.1182/blood.v99.4.1398
|View full text |Cite
|
Sign up to set email alerts
|

BCL10 mutation does not represent an important pathogenic mechanism in gastric MALT-type lymphoma, and the presence of the API2-MLT fusion is associated with aberrant nuclear BCL10 expression

Abstract: Two recurrent translocations have been associated with mucosa-associated lymphoid tissue (MALT) -type lymphoma, t(11; 18)(q21;q21) and t(1;14)(p22;q32). The first, t(11;18)(q21;q21), results in the fusion protein API2-MLT (API2-MALT1). Through t(1;14)(p22;q32), the BCL10 gene is entirely transferred to the IgH gene, resulting in its overexpression. Wild-type BCL10 is implicated in apoptosis, and it has been suggested that mutated forms gain oncogenic activity. The occurrence of genomic BCL10 mutations in 35 ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 28 publications
6
54
0
1
Order By: Relevance
“…79 Moderate nuclear expression of BCL10 is also observed in nearly 100% of MALT lymphomas with the other translocation, t(11;18). [80][81][82] On the basis of these findings, it has been suggested that the aberrant nuclear expression of BCL10 may be involved in the pathogenesis of MALT lymphoma.…”
Section: Molecular Pathogenesis Of Malt Lymphoma M Nakagawa Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…79 Moderate nuclear expression of BCL10 is also observed in nearly 100% of MALT lymphomas with the other translocation, t(11;18). [80][81][82] On the basis of these findings, it has been suggested that the aberrant nuclear expression of BCL10 may be involved in the pathogenesis of MALT lymphoma.…”
Section: Molecular Pathogenesis Of Malt Lymphoma M Nakagawa Et Almentioning
confidence: 99%
“…113 Several immunohistological studies have demonstrated the subcellular localization of BCL10 in MALT lymphoma cases. [79][80][81] However, the mechanism of this localization of BCL10 is not yet fully understood, thus prompting us to examine the subcellular localization of BCL10 in COS7 cells, where we found that BCL10 was localized in both cytoplasm and nucleus. 113 Our examination of subcellular localization of both BCL10 and MALT1 in a co-transfection system found that these two proteins are colocalized in the cytoplasm only, but, intriguingly, that the NES-specific inhibitor, leptomycin B, treatment has changed their subcellular localization from the cytoplasm to the nucleus.…”
Section: Two Signaling Pathways Underlying the Antiapoptotic Effect Bmentioning
confidence: 99%
“…Part of these cases was included in previous studies. 5,7,9,[14][15][16][17] Gastric endoscopic biopsies were included in this study on condition that clonal Ig heavy chain rearrangement was demonstrated to support the diagnosis of a MALT lymphoma. All cases were reviewed and diagnosed as extranodal marginal zone lymphomas according to the recent criteria of the WHO.…”
Section: Case Selectionmentioning
confidence: 99%
“…Nuclear BCL10 expression has been linked to the presence of t(1;14)(p22;q32) or t(11;18)(q21;q21), but the mechanisms of the aberrant nuclear localisation of BCL10 in malignant B cells remain unclear. 5,6 The MALT1 gene is directly involved in the MALT lymphoma-associated chromosomal translocations t(11;18)(q21;q21) and t(14;18)(q32;q21). The first translocation is the most common structural chromosomal abnormality in gastric MALT lymphoma.…”
mentioning
confidence: 99%
“…Actin polymerization then appeared to be a key factor in the migration of microclusters. Interestingly, the adaptor ADAP is linked to the actin cytoskeleton and, upon antigenic stimulation, is recruited to the actin-rich periphery of the immune synapse, where it associates with the microtubule motor dynein [107]. Furthermore, ADAP was shown to play a role in the relocation of the MTOC to the IS through its interaction with dynein.…”
Section: Molecular Requirements For the Polarization Of The Ismentioning
confidence: 99%